2008
DOI: 10.1002/ajh.21256
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression and clinical significance of P‐glycoprotein in previously untreated extranodal NK/T‐cell lymphoma, nasal type

Abstract: Overexpression of P-glycoprotein (P-gp) has been identified by a variety of methods in NK cells and NK malignancies. The aim of this study was to determine the clinical significance of P-gp in previously untreated extranodal NK/T-cell lymphoma, nasal type. Tumor specimens from 30 patients initially treated with CHOP or CHOP-based chemotherapy were examined by immunohistochemistry using JSB-1, a monoclonal antibody recognizing the intracellular epitope of P-gp molecule. Twenty cases (67%) were positive for P-gp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 26 publications
0
75
0
2
Order By: Relevance
“…2 P-gp has been related to the intrinsic and acquired drug resistance in several neoplasms and represents one of the leading cause of the failure of chemotherapeutic treatments and poor prognosis of cancer. 3,4 In the gastrointestinal tract, under physiological conditions, P-gp expression progressively decreases from ileum, where it shows the maximum level of expression, to the stomach where it is absent. 5 In contrast, P-gp is generally overexpressed in gastric cancer (GC), where it has been traditionally linked to poor prognosis and multidrug resistance.…”
mentioning
confidence: 99%
“…2 P-gp has been related to the intrinsic and acquired drug resistance in several neoplasms and represents one of the leading cause of the failure of chemotherapeutic treatments and poor prognosis of cancer. 3,4 In the gastrointestinal tract, under physiological conditions, P-gp expression progressively decreases from ileum, where it shows the maximum level of expression, to the stomach where it is absent. 5 In contrast, P-gp is generally overexpressed in gastric cancer (GC), where it has been traditionally linked to poor prognosis and multidrug resistance.…”
mentioning
confidence: 99%
“…The median follow-up for all the patients was 22 months and the median PFS and OS were not attained. Wang et al (8) reported that 67% of the patients were positive for P-gp expression and the CR rate achieved in P-gp-positive patients was significantly lower compared to that in P-gp-negative patients (20 vs. 60%, respectively; P=0.045) when treated with a cyclophosphamide, adriamycin, vincristine and prednisone (CHOP)-like regimen. As adriamycin and vincristine are substrates for P-gp, Yong et al (23) reported that ENKTCL patients treated with CHOP regimen followed by IFRT exhibited a CR rate of only 27%.…”
Section: Discussionmentioning
confidence: 99%
“…An optimal treatment for ENKTCL has not yet been established, particularly for advanced-stage disease. The low treatment efficacy may be mainly attributed to the fact that this disease is resistant to several chemotherapeutic agents, due to the expression of P-glycoprotein (P-gp) (8,9). Therefore, investigations have been focused on improving the efficacy of chemotherapy and reducing the risk of disease recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…None of the studies were confirmatory in nature, and those are the only ones in which clinical application can be found. Schreck et al [75] demonstrate that a large number of Th2 cells in HL is related to better survival; Dong et al [76] show that bcl10 expression (next to t (11;14)) is related to HP-eradication unresponsiveness; according to Wang et al [77], cytoplasmic sox11-expressing MCLs have a poorer survival; mutation nor polymorphism of the CD20 gene is predicting rituximab response (Sar et al [78]); Aktas et al [79] show that high apoptotic index is related to good prognosis in pediatric lymphomas; Lenz et al [80] describes new gene signatures that predict therapy response in DLBL; Peh et al [81] found that bcl-6 expression is associated with poor survival in DLBL and immunohistochemically determined ABC not; according to Johnson et al [82], DLBL with low CD20 expression have lower survival rate; Ki67 and Pim1 are independent indicators of poor survival in MCL (Hsi et al [83]); low Ki67 is a negative predictor of survival in DLBL (Hasselblom et al [84]); SIRT1 expression is associated with poor prognosis in DLBL (Jang et al [85]); in FL, Johnson et al [86] show that secondary genetic alterations indicate aggressive behavior; Hasselblom et al [87] show that the number of CD68-positive cells in DLBL does not predict prognosis; TCL1A is associated with more aggressive clinical behavior in CLL and MCL according to Aggarwal et al [88]; aberrations in the MYC locus are associated with poor outcome in DLBL (Klapper et al [89] and Yoon et al [90]); expression of P-glycoprotein indicates therapy unresponsiveness in nasal type NK/T cell lymphoma according to Wang et al [91];…”
Section: Prognostic Factors In Lymphomamentioning
confidence: 99%